PENYELESAIAN PERKARA PERSELISIHAN DALAM RUMAH TANGGA SECARA PERADILAN ADAT DI GAMPONG SEUTUI KECAMATAN BAITURRAHMAN KOTA BANDA ACEH - Saleh, Rahman; Ismi, Hayatul; ', Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
In solving the problems that exist within the Gampong community, Keuchik as the supreme leader must coordinate with all officers of Gampong, Keuchik must also coordinate with the security and public order security (Babinkamtibmas) or the Community Police (Polmas). Coordination between the Gampong (Keuchik) Judiciary and Police officers is very much in line with the Community Police Partnership Forum (FKPM) program. In connection with the above description there are many cases of minor maltreatment that have been carried out peace efforts through customary institutions / justice as regulated in Qanun Aceh no. 9 of 2008.The purpose of this thesis writing is: First, To know the Stages of Settlement Case Disputes In Households by Traditional Court In Gampong Seutui Baiturrahman Sub-district City of Banda Aceh. Secondly, to know the existence of the settlement of cases of disputes within the household by customary court in Gampong Seutui Baiturrahman sub-district of Banda Aceh city has provided justice between the parties.The type of this research is sociological juridical research which means to review the condition of existing problems in the field is related to the applicable legal aspects and which regulate the problem.From the result of the research, it is concluded that Firstly, the stage of settling the case of disputes within the household by customary court in Gampong Seutui Baiturrahman Sub-district of Banda Aceh City is in the implementation of custom settlement there are stages or gradually in the process of settlement and there are customary sanctions provided by the community. The stage starts from the keuchik level, then, tuha peut, then the mukim as the final place of completion in adat. and the time given at all levels by the government is 1 month. And if the case is not resolved customarily then it will be taken by the competent authority to settle the matter legally in force. Second, the settlement of cases of disputes within the household by customary court in Gampong Seutui Baiturrahman Sub-district City of Banda Aceh Giving the justice between the parties is basically giving justice between the parties caused by the parties have taken the agreement to make the peace so that the agreement has given the legal certainty of both the victim who has been harmed and the perpetrator who must fulfill the agreement will not repeat his actions and if the perpetrators repeat it then there is a legal threat to be prosecuted under applicable law.Keywords: Settlement of Household Disputes, Traditional Court of Gampong